2022
DOI: 10.4028/p-6849u0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, Biological Evaluation, and Assessment Laser Efficacy for New Derivatives of Tetrazole

Abstract: In this study, new tetrazole [A1-A5] were prepared by the reaction of Schiff base with sodium azide in tetrahydrofuran (THF) by the traditional method (reflux) and microwave technology. The prepared compounds were characterized by physical properties, UV-Vis, FT-IR, 1H-NMR, 13C-NMR spectral, and C.H.N analysis. TLC checked the purity of these compounds. Antibacterial behaviors were investigated against a variety of bacteria, including Escherichia coli, and Klebsiella pneumonia Gram (-) ve, Staphylococcus aureu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Effect of oxidizing agent volume: Increasing volume of the oxidizing agent was used with a concentration of 0.001 molar to find out the volume that gives the highest absorption, and the results are shown in Figure (5), as it was found that the best volume of acid added is (1ml) 3) by adopting the same optimal conditions, where the time 10 minutes was sufficient to complete the oxidation process. Calibration curve: The calibration curve for (Cef) with P-aminobenzoicacid showed the linearity at concentrations rang of (5-75) μg/ml, as show in figure (6).…”
Section: Optimal Conditionsmentioning
confidence: 89%
See 3 more Smart Citations
“…Effect of oxidizing agent volume: Increasing volume of the oxidizing agent was used with a concentration of 0.001 molar to find out the volume that gives the highest absorption, and the results are shown in Figure (5), as it was found that the best volume of acid added is (1ml) 3) by adopting the same optimal conditions, where the time 10 minutes was sufficient to complete the oxidation process. Calibration curve: The calibration curve for (Cef) with P-aminobenzoicacid showed the linearity at concentrations rang of (5-75) μg/ml, as show in figure (6).…”
Section: Optimal Conditionsmentioning
confidence: 89%
“…Effect of base volume: The volume that delivers the maximum absorption was determined by adding increasing volumes of NaOH at a concentration of 1.0 molar, with the optimal volume added from the base being 0.5 m. 0M each of them, as well as the same added volume of 0.5 ml, were used to find out which base gives the best absorption when forming a total, as it was found that the best M base is NaOH, and it is shown in Table (6) Table ( 6 Effect of Time: The effect of product stability was investigated for its significance in determining the period of time during which it remains constant, as well as the interaction that time was followed using optimum conditions every ten minutes for 30 minutes. Effect of oxidation time: The time at which the drug is oxidized using the oxidizing agent NBS was studied, and before completing the rest of the additions and completing the volume in the volumetric vial, and the results are shown in Table (8), depending on the same optimal conditions, where the time 10 minutes was sufficient to complete the oxidation process.…”
Section: Study the Optimal Conditions For The Formation Of The Productmentioning
confidence: 99%
See 2 more Smart Citations
“…Figures (30 -23) show that the compound [WS.X1] increased the inhibition values against all types of bacteria; This is because the compound is aliphatic, and despite the decrease in the basicity, there was an increase in the inhibition values; This is due to the presence of (CH2) groups of electrons. For compound [WS.X4], the highest braking rate was obtained; This appears to be due to atoms of heterogeneous groups such as (N, S, O) despite the low basicity [28].…”
Section: Biological Activitymentioning
confidence: 99%